The critics of false culture: On the Finnish reception of the Enlightenment - Heli Rantala (Approaching Religion, 2011)
Heli Rantala’s contribution discusses the heritage of the Enlightenment from the perspective of Finnish nineteenth century cultural discourse. She argues that the Finnish reception of the Enlightenment had a negative tone. This critical attitude was expressed amongst Finnish intellectuals throughout the nineteenth century. The main target of the critique was the French style Enlightenment and the French way of life in general, which was understood to be civilised but lacking in the idea of real culture. Rantala also states that J. V. Snellman opposed this dominant interpretation by highlighting the importance of the Enlightenment era and by cherishing the basic values of its ideas.